Influência da vacuoterapia nos graus de classificação da celulite e dor - Barbosa, Maciel; Melo, Cristina Argel de (My University, 2011)
Background: Most post-puberty women exhibit cellulite, particularly in the thigh and buttock regions. The purposes of this semi-controlled trial were to evaluate the effectiveness of vacuotherapy on cellulite and its associated pain, and analysis of the possible statistic relationship between the use of birth control pill and the cellulite grades. Methods: Sixteen young women with a mean age of 21 and a body mass index of 22 were randomly split-half into two groups of 8 participants each, one experimental-group (EG) which received 10 sessions of vacuotherapy, and one control-group (CG) that didn’t received any treatment. The grade of cellulite was assessed in the two groups, by three experienced experts using standardized digital photography based on one observational graduation scale. The pain caused by vacuotherapy in EG was measured with the numeric pain scale (NPS) and the consumption of birth control pill by a questionnaire. Results: On the experimental group was observed a statistically significant reduction of grades of cellulite comparing to control group (U = 12,0; p = 0,03). The consumption of birth control pill has a statistically significant influence on the grade of cellulite (r = 0,7 p ˂ 0,0001). The pain caused by vacuotherapy statistically decreased between first and last treatment session (Z=2,530; p=0,011). Conclusion: Vacuotherapy seems to be effective on the reduction of cellulite and its associated pain in this study sample. The consumption of birth control pill is related to cellulite grades.